PENINGKATAN HASIL BELAJAR IPAS PESERTA DIDIK MELALUI PENDEKATAN TPACK BERBANTUAN MEDIA AUGMENTED REALITY KELAS V SD - Asri Rahmawati; Sandi Budiana; Hida Wahida Chusen (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
This Collaborative Classroom Action Research (PTKK) aims to find out and get data on how to improve IPAS learning outcomes about the human visual system for grade V students of SDN Kawung Luwuk in semester 1 of the 2023/2024 academic year through the TPACK approach and Augmented Reality media.This research departs from the results of observations of the problems of grade V students at SDN Kawungluwuk, namely there are several concepts in the subject matter that are still considered difficult or abstract for students. This can be a challenge for educators in explaining the material effectively and ensuring students' understanding. The value of media effectiveness is obtained from the response of students or respondents when using the media and comprehension tests after getting the material of the human visual system and ecosystems with Augmented Reality media. Learning outcomes obtained by students in each cycle. In cycle I with the average value of learning outcomes obtained by 71 and in cycle II the average value increased to 85. As for the presentation of completeness in cycle I 63% and in cycle II reached 88% exceeding the predetermined research success indicator of 85%. Based on research that has been conducted by researchers at Kawungluwuk State Elementary School on the Application of the TPACK approach and Augmented Reality media to Improve Learning Outcomes of IPAS subjects, it is generally concluded that the application of the learning model has succeeded in providing an increase in learning outcomes in class V-A students of SDN Kawungluwuk.